2016
DOI: 10.1007/s40415-016-0286-7
|View full text |Cite
|
Sign up to set email alerts
|

The austral thrush (Turdus falcklandii) reduces the seed germination for the urban ornamental tree glossy privet (Ligustrum lucidum) in Santiago, Chile

Abstract: Seed dispersal by endozoochory is an important mechanism promoting the spread of exotic fleshy-fruit plants. Although the invasiveness of glossy privet (Ligustrum lucidum W.T. Aiton) in several regions has been associated with the presence of disperser birds, only a few studies have examined their seed germination after dispersal. In Central Chile, the privet grown is an ornamental species, but to date, it has not been observed to settle in natural or seminatural habitats. In Santiago city, the fruits of gloss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Similar results were observed when Solanum mauritianum, Cinnamomum camphora, Psidium guajava, and Morus alba L., were fed to Knysna (Tauraco corythaix) and Purple-crested Turacos in which germination success was unaffected(Thabethe et al 2015). Contrary results were reported whenCastro et al (2016) found that germination success of the glossy privet tree Ligustrum lucidum W.T. Aiton.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Similar results were observed when Solanum mauritianum, Cinnamomum camphora, Psidium guajava, and Morus alba L., were fed to Knysna (Tauraco corythaix) and Purple-crested Turacos in which germination success was unaffected(Thabethe et al 2015). Contrary results were reported whenCastro et al (2016) found that germination success of the glossy privet tree Ligustrum lucidum W.T. Aiton.…”
supporting
confidence: 66%
“…Such contrasts show that seeds of different plant species respond differently to ingestion by different bird species and, therefore, affect germination. Findings presented in our study highlight the importance of frugivorous bird species in facilitating the spread of IAPs (Castro et al 2016). Factors that might have affected the results are highlighted in a review by Traveset (1998), including size and thickness of the seed coat, differences in gut passage times, diets of birds, and seed age.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies indicated that frugivorous birds were seed dispersers and/or predators of Ligustrum species (MacRae 1980; Castro et al . 2016; Fernandez et al . 2020).…”
Section: Figurementioning
confidence: 99%
“…In general, seed dispersal brings 3 main benefits to plants (Howe & Smallwood 1982): (i) escape from seed predators, pathogens, or seedling competition; (ii) colonization of new habitats; and (iii) directed dispersal to specific sites. Previous studies indicated that frugivorous birds were seed dispersers and/or predators of Ligustrum species (MacRae 1980;Castro et al 2016;Fernandez et al 2020). Therefore, the ecological functions of frugivorous birds to seeds or O. suturalis weevils should be variable according to different contexts.…”
mentioning
confidence: 99%